2016
DOI: 10.1037/abn0000148
|View full text |Cite
|
Sign up to set email alerts
|

Superior orientation discrimination and increased peak gamma frequency in autism spectrum conditions.

Abstract: While perception is recognised as being atypical in individuals with autism spectrum conditions (ASC), the underlying mechanisms for such atypicality are unclear. Here we test the hypothesis that individuals with ASC will show enhanced orientation discrimination compared to neurotypical observers. This prediction is based both on anecdotal report of superior discriminatory skills in ASC and also on evidence in the auditory domain that some individuals with ASC have superior pitch discrimination. In order to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 83 publications
7
54
3
Order By: Relevance
“…In this study, slower binocular rivalry indicated disruption to E/I balance in ASD, although no group differences were found in occipital GABA levels. Dickinson et al (2016) found a significant difference between orientation discrimination thresholds and peak gamma frequency in ASD, concluding that both variables pointed towards increased inhibition in ASD. Future studies could be much more ambitious in this regard, and it is hoped that future researchers will be able to obtain data from multiple methodologies from the same individual in order to more clearly identify the way in which E/I balance is altered in ASD (if at all).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, slower binocular rivalry indicated disruption to E/I balance in ASD, although no group differences were found in occipital GABA levels. Dickinson et al (2016) found a significant difference between orientation discrimination thresholds and peak gamma frequency in ASD, concluding that both variables pointed towards increased inhibition in ASD. Future studies could be much more ambitious in this regard, and it is hoped that future researchers will be able to obtain data from multiple methodologies from the same individual in order to more clearly identify the way in which E/I balance is altered in ASD (if at all).…”
Section: Resultsmentioning
confidence: 80%
“…We have recently found that orientation discrimination thresholds are decreased in adults with ASD (Dickinson et al, 2016, although see Schwarzkopf, Anderson, de Haas, White, & Rees, 2014Shafai, Armstrong, Iarocci, & Oruc, 2015), and also that orientation discrimination thresholds correlate with autistic traits in the neurotypical population (Dickinson, Jones, & Milne, 2014). Inhibitory mechanisms are implicated in orientation discrimination as they are known to be involved in tuning the orientation selectivity of cells, as orientation selective neurons become narrowly tuned to a particular orientation through lateral inhibition (Hubel & Wiesel, 1968), and GABAergic inhibition has been shown to directly influence orientation discrimination ability.…”
Section: Perceptual Discriminationmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work has found superior orientation discrimination in individuals with ASD (Dickinson et al 2016). In contrast to the current work, this study employed an adaptive staircase which converged on 79% correct to measure perceptual thresholds (Dickinson et al 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Some of the participants (17 with ASD and 9 NT controls) had taken part in our previous study measuring orientation discrimination (Dickinson et al, 2016).…”
Section: Methods Participantsmentioning
confidence: 99%